Neurogenic Bladder Repair Using Autologous Mesenchymal Stem Cells - Pradeep V. Mahajan; Swetha Subramanian; Amit Danke; Anand Kumar (Case Reports in Urology)
The normal function of the urinary bladder is to store and expel urine in a coordinated, controlled fashion, the activity of which is regulated by the central and peripheral nervous systems. Neurogenic bladder is a term applied to a malfunctioning urinary bladder due to neurologic dysfunction or insult emanating from internal or external trauma, disease, or injury. This report describes a case of neurogenic bladder following laminectomy procedure and long-standing diabetes mellitus with neuropathy treated with autologous cellular therapy. The differentiation potential and paracrine effects of mesenchymal stem cells on bladder function have been highlighted.